Mahasiswa dan Internet: Dua Sisi Mata Uang? Problematic Internet Use pada Mahasiswa - Reynaldo Reynaldo; Yasinta Astin Sokang (Faculty of Psychology, Universitas Gadjah Mada, 2016)
Problematic Internet Use (PIU) is one of the negative effects of the internet use, but we can rarely find publications on PIU of Indonesian’s college students, especially college students in Jakarta. The purpose of this research was to describe PIU among college students in Jakarta. The Generalized Problematic Internet Use Scale 2 was used to collect data of a total of 474 college students from three universities in Jakarta. The results showed that: a) For preference for online social interaction symptoms, participants preferred to do online social interaction rather than face to face interaction, especially when face to face interactions were not possible. b) For mood regulation symptoms, participants used internet to regulate their negative feelings. c) For cognitive preoccupation symptoms, participants tended to have obsessive thought patterns for their activity on internet. d) For compulsive internet use symptoms, participants found it difficult to restrict their internet use. e) For negative outcome symptoms, online activities of participants did not have negative influence on their daily routines. Furthermore, the results showed no significant differences of the PIU symptoms across gender and internet use duration. Taken together, the results indicated moderate level of problematic internet use in our sample